One‐Step Synthesis of Hybrid Core–Shell Metal–Organic Frameworks. (12th March 2018) - Yang, Xinyu; Yuan, Shuai; Zou, Lanfang; Drake, Hannah; Zhang, Yingmu; Qin, Junsheng; Alsalme, Ali; Zhou, Hong‐Cai
Abstract: Epitaxial growth of MOF‐on‐MOF composite is an evolving research topic in the quest for multifunctional materials. In previously reported methods, the core–shell MOFs were synthesized via a stepwise strategy that involved growing the shell‐MOFs on top of the preformed core‐MOFs with matched lattice parameters. However, the inconvenient stepwise synthesis and the strict lattice‐matching requirement have limited the preparation of core–shell MOFs. Herein, we demonstrate that hybrid core–shell MOFs with mismatching lattices can be synthesized under the guidance of nucleation kinetic analysis. A series of MOF composites with mesoporous core and microporous shell were constructed and characterized by optical microscopy, powder X‐ray diffraction, gas sorption measurement, and scanning electron microscopy. Isoreticular expansion of microporous shells and orthogonal modification of the core was realized to produce multifunctional MOF composites, which acted as size selective catalysts for olefin epoxidation with high activity and selectivity.